The nationalist movements in Spain, today: a Catalonian and Basque comparison - Carvalho, Catarina L. (2021)
Pro-independence movements in the Basque Country and in Catalonia have old historical roots. Whereas in Catalonia the pro-independence social mobilization has recently gained energy, in the Basque Country it seems less prominent nowadays. We explore the psychosocial predictors associated with individuals’ involvement in collective efforts towards independence in both these contexts. We distributed an online questionnaire among Basque (n=132) and Catalonian (n=152) independence supporters. Among the Basque independence supporters, pro-independence collective action tendencies were negatively predicted by perceived social status and identification with Spain, and positively predicted by patriotism and collective efficacy. Among the pro-independence Catalonians, only identification with Catalonia and collective efficacy beliefs predicted pro-independence collective action tendencies. These results are discussed considering historical, political, and socioeconomic factors.